2010
DOI: 10.1111/j.1478-3231.2010.02331.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and causes of discordance in fibrosis staging by transient elastography and liver biopsy

Abstract: Discordance between liver fibrosis estimated by TE and biopsy occurs in one in seven patients. In assessing the validity of TE results, clinicians must recognize risk factors for discordance and in at-risk patients, consider alternative measures including biomarkers and possibly biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
93
6
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 34 publications
16
93
6
2
Order By: Relevance
“…Indeed, only when this criterion was not fulfilled, the sensitivity of the method significantly decreased. On the other hand, by using VCTE and liver biopsy as the reference standard, it has been shown that the number of measurements or the success rate had no significant influence on the staging of liver fibrosis [6,9,10]. In particular, Kettaneh et al compared the AUROCs for the prediction of cirrhosis between the median values of the 3 first, the 5 first and the 10 first successful shots of VCTE and reported that there was no significant loss in performance if only 5 valid shots were obtained [10].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, only when this criterion was not fulfilled, the sensitivity of the method significantly decreased. On the other hand, by using VCTE and liver biopsy as the reference standard, it has been shown that the number of measurements or the success rate had no significant influence on the staging of liver fibrosis [6,9,10]. In particular, Kettaneh et al compared the AUROCs for the prediction of cirrhosis between the median values of the 3 first, the 5 first and the 10 first successful shots of VCTE and reported that there was no significant loss in performance if only 5 valid shots were obtained [10].…”
Section: Discussionmentioning
confidence: 99%
“…TE has been validated in different liver diseases and has been shown to be accurate in diagnosing fibrosis in the F3-F4 stages with a specificity of 72 % and sensitivity of 86 % [5]. Previous studies have demonstrated that the patient's anthropometric characteristics and etiology of liver disease are factors that can influence the reliability of TE measurements and that these factors may influence the diagnosis of liver fibrosis [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…No significant loss in performance was reported if only 5 valid acquisitions were obtained. It is likely that IQR/M is the key factor for discordance between TE and histological fibrosis stage [79,80]. In a recent large population study, new reliability criteria based on IQR/M and median LSMs were proposed [81].…”
Section: How To Measure?mentioning
confidence: 99%
“…An IQR/M ≤ 30 % of the 10 measurements is the most important reliability criterion (LoE 1b, GoR A) [79,80]. Strong consensus (17/0/0, 100 %) This document was downloaded for personal use only.…”
Section: Recommendationmentioning
confidence: 99%